(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the difference between the effect of nitroglycerin on the aortic stiffness measured by transthoracic M-mode ultrasonography in patients with and without coronary artery disease (CAD).Material and Methods: This study was conducted on one hundredpatients with a presume diagnosis of CAD. The patients who had a SYNTAX score (SS) ≥1 according to the results of coronary angiography constituted the CAD group (n:60), while patients who had a SS=0 constituted the control group (n:40).The stiffness of the ascending aorta and arterial blood pressure were measured before and 10 minutes after the sublingual administration of 800 mcg nitroglycerin. A comparison of each parameter before and after nitroglycerin was evaluated for statistical significance using paired sample t-test.Results: In the control group, after nitroglycerin administration, there was a statistically significant reduction in the pulsatile diameter change (from 2.30±0.79 to 1.74±0.91) and significant increase in stiffness index (from 6.24±2.41 to 9.07±5.88). In the CAD group, after nitroglycerin administration, there wasno statistically significant difference in terms of pulsatile diameter change (from 1.42±0.88 to 1.28±0.68) and stiffness index (from 13.52±7.64 to 13.10±7.85).Conclusion: The effect of nitroglycerin on the aortic stiffness measured by transthoracic M-mode ultrasonography differs in the CAD and control groups. Our findings warrant further studies with a larger population to describe the practicability of this method for the CAD diagnosis.Keywords: Aorta; Coronary Artery Disease; Stiffness; Nitroglycerin.